2021
DOI: 10.1128/aem.01801-21
|View full text |Cite
|
Sign up to set email alerts
|

Independent Evolution of a Lysergic Acid Amide in Aspergillus Species

Abstract: Ergot alkaloids derived from lysergic acid have impacted humanity as contaminants of crops and as the bases of pharmaceuticals prescribed to treat dementia, migraines, and other disorders. Several plant-associated fungi in the Clavicipitaceae produce lysergic acid derivatives, but many of these fungi are difficult to culture and manipulate. Some Aspergillus species, which may be more ideal experimental and industrial organisms, contain an alternate branch of the ergot alkaloid pathway b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 41 publications
1
13
0
2
Order By: Relevance
“…To date all genes required for ergot alkaloid synthesis have been encoded in the eas cluster [ 2 , 3 , 7 , 8 ]. In a recent study relevant to this point, Jones et al [ 10 ] reported that three species of Aspergillus synthesize LAH and evolved the steps for incorporation of lysergic acid into LAH independently of M. brunneum (and other fungi in the Clavicipitaceae) yet had similarly constituted eas clusters with no additional genes present that might be redundant with easP . The possibility that two lineages evolved similar pathways for incorporating lysergic acid into LAH yet kept one unrelated and redundant gene outside the eas cluster appears unlikely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date all genes required for ergot alkaloid synthesis have been encoded in the eas cluster [ 2 , 3 , 7 , 8 ]. In a recent study relevant to this point, Jones et al [ 10 ] reported that three species of Aspergillus synthesize LAH and evolved the steps for incorporation of lysergic acid into LAH independently of M. brunneum (and other fungi in the Clavicipitaceae) yet had similarly constituted eas clusters with no additional genes present that might be redundant with easP . The possibility that two lineages evolved similar pathways for incorporating lysergic acid into LAH yet kept one unrelated and redundant gene outside the eas cluster appears unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…In fungi that produce LAH as well as ergonovine (e.g., M. brunneum , the paspalum ergot fungus Claviceps paspali , and the morning glory symbiont Periglandula ipomoeae ) there are two additional genes in the eas cluster: easO , encoding a Baeyer–Villiger monooxygenase (BVMO) required for synthesis of LAH [ 6 ], and easP , encoding an α/β hydrolase fold protein, a role for which in ergot alkaloid synthesis has not yet been demonstrated but whose presence correlates perfectly with the ability to produce LAH [ 7 , 8 , 10 ]. As a BVMO, EasO is hypothesized to insert an oxygen between the alpha carbon and carbonyl carbon of the alanyl portion of lysergyl-alanine [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…One aspect of the genes involved in ergot alkaloid biosynthesis that greatly facilitates research is that the genes are clustered in the genomes of producing fungi (Figure 2 ). These gene clusters (referred to as eas clusters, for ergot alkaloid synthesis; Schardl et al, 2006 ) contain core genes that are common to multiple ergot alkaloid producers as well as branch‐specific genes required for producing the unique alkaloids found in different fungi (Fabian et al, 2018 ; Haarmann et al, 2005 ; Jones et al, 2021 ; Martín et al, 2017 ; Schardl, Young, Hesse, et al, 2013 ; Schardl, Young, Pan, et al, 2013 ; Tudzynski et al, 1999 ). Thus, as the functions of genes in various pathway branches are determined, the values of gene clusters increase as predictors of ergot alkaloid biosynthesis capacity and as sources of genes controlling certain biochemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…К л а с т е р г е н о в б и о п р о д у к ц и и а л к а л о и д о в. О кластерной организации генов биосинтеза алкалоидов у спорыньи впервые сообщили в 1999 году, и в частности было показано значение гена dmaW для биосинтеза (8,102). Кластеры генов биосинтеза эргоалкалоидов обнаружены у различных грибов (30), например у Clavicipitaceae (30,103,104), в частности у Claviceps (30,102,103), Epichloe (20,30), Periglandula (3), Metarhizium brunneum (86,105), Neotyphodium lolli (106), Balansia cyperi, Balansia obtecta (30); у Aspergillus (107,108), в частности у Aspergillus fumigatus (107,110), A. leporis, A. homomorphus, A. hancockii (111) и A. japonicus (112,113); у Clavulinopsis fusiformis (106); у Arthroderma benhamiae (114,115); у Penicillium camemberti и Penicillium biforme (116).…”
unclassified